La relación entre religión, espiritualidad y salud: una revisión crítica desde las ciencias sociales (2021)
This article presents a critical review of the scientific literature on the effects of spirituality and religiousness on human health. Through a hermeneutical analysis of the texts, it was found that this type of literature lacks sufficiently clear and consensual definitions of the analytical concepts and categories. For this reason, the article resorts to the contributions of different social science research on religious phenomena and, especially, on the advent and growing diffusion of the concept of spirituality in contemporary Western societies. It is concluded that a new theoretical-methodological framework is necessary to account for the individualized and deinstitutionalized beliefs typical of late modernity, and new hypothesis are proposed on the causal relationship between spirituality and health. Finally, the need to implement a phenomenology of spirituality is recommended, in order to improve our understanding of the meanings and experiences that local populations associate with the concept of spirituality.